2016
DOI: 10.1111/jdi.12531
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant type 1 diabetes mellitus with anti‐programmed cell death‐1 therapy

Abstract: Anti-programmed cell death-1 (PD-1) antibodies are regarded as a risk factor for insulindependent diabetes mellitus as a side-effect. While a small number of cases have been reported, evidence remains limited. This is the first report of an Asian patient developing insulin-dependent diabetes during anti-PD-1 therapy. A 55-year-old euglycemic woman receiving nivolumab for malignant melanoma showed abrupt onset of ketonuria, and elevated levels of plasma glucose (580 mg/dL) and hemoglobin A1c (7.0%). Over the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 10 publications
0
100
2
6
Order By: Relevance
“…In the study of lambrolizumab, hyperglycemic events were not reported [37]; however, in patients treated with pembrolizumab after approval, hyperglycemic events were reported in 45% to 49% of patients, and 3% to 6% experienced grade 3 or 4 hyperglycemic events. Among 2,117 patients, fulminant type 1 diabetes mellitus (T1DM) occurred with an incidence rate of 0.1% and at various stages of treatment, ranging from 1 week to 12 months [4142]. …”
Section: Immunotherapy: Checkpoint Inhibitorsmentioning
confidence: 99%
“…In the study of lambrolizumab, hyperglycemic events were not reported [37]; however, in patients treated with pembrolizumab after approval, hyperglycemic events were reported in 45% to 49% of patients, and 3% to 6% experienced grade 3 or 4 hyperglycemic events. Among 2,117 patients, fulminant type 1 diabetes mellitus (T1DM) occurred with an incidence rate of 0.1% and at various stages of treatment, ranging from 1 week to 12 months [4142]. …”
Section: Immunotherapy: Checkpoint Inhibitorsmentioning
confidence: 99%
“…Only few cases of immunotherapy related fulminant diabetes mellitus have been reported so far. [35]…”
Section: Introductionmentioning
confidence: 99%
“…This mechanistic difference may help partially explain the fact that nivolumab is more tolerable and is associated with a significantly lower risk of severe treatment-related adverse events, compared to docetaxel. However, nivolumab is not entirely safe, as previous studies have revealed associations with increased risks of thyroid dysfunction, fulminant type 1 diabetes mellitus, and vitiligo 17,22,23 . Therefore, additional detailed clinical information and biomarkers are needed to predict these treatment-related adverse events in patients who receive nivolumab 17 .…”
Section: Discussionmentioning
confidence: 91%